QuickBooks 2017 : all-in-one - Nelson, Stephen L. (--For dummies., 2017)
Make business chores easy with QuickBooks Managing the books for a small business can be a challenging, onerous task. If you're looking to spend fewer hours hunched over multiple spreadsheets and more time focused on other aspects of your growing business, this all-in-one guide gives you everything you need to put QuickBooks to work for you. Combining eight content-rich books into one complete package, this value-priced reference provides answers to all the questions you have about how QuickBooks can manage your business finances--even the ones you didn't know to ask! With the help of QuickBooks 2017 All-In-One For Dummies , you'll quickly and painlessly discover how to use this fan-favorite software program to establish fundamental accounting practices that will keep your company successful and healthy. From installing the software and configuring QuickBooks to setting up payroll reminders and keeping track of your business checkbook and credit cards, everything you need to effectively--and efficiently--stay on top of those dollars and cents is only a page away! Organize all of your business finances in one place Pay vendors, invoice customers, and track inventory Prepare financial statements and reports Access your cloud-based account using your smartphone This is your all-encompassing guide to putting your financial woes to rest and simplifying your business accounting with confidence!